Russian Representative Institutions of the 16th-17th Centuries in the European Context: A Historiographical Perspective - Vladislav Dmítrievich NAZÁROV; Pável Yúrievich OUVÁROV; Vladímir Aleksándrovich VÉDYUSHKIN (Studia Historica: Historia Moderna, 2015)
The article deals with the history of the origins and development of Zemsky Sobors – Russian representative institutions, their main features and differences from corresponding bodies in Western Europe. It marks out those traits of Russian history that determined the character and development dynamics of Zemsky Sobors, shows a connection between their heyday and specific condition of Russian society and state during the Time of Troubles, and describes some sources for this subject. The focus of the article is on Russian research of the history of representative institutions in Russia and Western Europe. It also investigates a close attention to European historical experience, inherent in the Russian social thought. In this context reasons for the origin and existence of the term of «estaterepresentative monarchy», characteristic for the Russian historiography, are analysed. And the main periods of the study of representative institutions from the mid-19th century to the present day are determined and characterised. The article considers the outcome of a Moscow conference of 2013 devoted to the representative Institutions of Russia in the european context and outlines perspectives of further research.